Biogenic silver nanoparticles synthesized from Pseudomonas fluorescens-mediated olive cake waste: antimicrobial, larvicidal activity against Culex pipiens and cytotoxicity assessment - Samah H. Abu-Hussien; Muhammad A. Khan; Ammar AL-Farga; Ahmed G. Soliman; Salwa M. El-Sayed; Eslam Adly (BMC Biotechnology)
Abstract This study presents an eco-friendly approach for synthesizing silver nanoparticles (AgNPs) using olive cake hydrolysate (OCH), produced through microbial fermentation of olive cake waste by Pseudomonas fluorescens. The OCH was analyzed by gas chromatography–mass spectrometry (GC–MS), revealing the biotransformation of olive cake components into bioactive compounds, including 24-norursa-3,12-diene, methyl esters of 9,12-octadecadienoic acid and 9-octadecenoic acid, and α-sitosterol. The biosynthesized olive cake hydrolysate-silver nanoparticles (OCH-AgNPs) were characterized using ultraviolet–visible (UV–Vis) spectroscopy to confirm surface plasmon resonance at 420 nm; Fourier-transform infrared (FTIR) spectroscopy to identify the involvement of hydroxyl and carbonyl functional groups; X-ray diffraction (XRD) analysis to verify the crystalline structure, revealing prominent (111) lattice planes of face-centered cubic (fcc) silver; transmission electron microscopy (TEM) to assess morphology and particle size, showing spherical nanoparticles with an average diameter of 19.6 ± 6.1 nm; dynamic light scattering (DLS) to measure hydrodynamic diameter, yielding a size of 109.8 nm; and zeta potential analysis to determine surface charge, which indicated high colloidal stability with a zeta potential of − 47.0 mV. OCH-AgNPs exhibited superior antimicrobial activity compared to OCH alone, with low MIC values against P. aeruginosa, Candida albicans, Aspergillus brasiliensis, and Staphylococcus aureus MRSA. Larvicidal activity, optimized via Box–Behnken design, showed 98.86% mortality of Culex pipiens at 1.0 µg/mL (LC₅₀ = 0.40 µg/mL), significantly outperforming OCH (LC₅₀ = 57.22 µg/mL). Histopathological and biochemical analyses of treated larvae revealed structural damage, decreased protein and carbohydrate content, and inhibition of acetylcholinesterase. Cytotoxicity assays on human skin fibroblasts confirmed low toxicity (IC₅₀ >200 µg/mL). Molecular docking identified α-sitosterol as a key bioactive component. These findings underscore the potential of OCH-AgNPs as a sustainable and multifunctional biocontrol agent for microbial and vector management. Graphical Abstract